Thermal and mechanical properties of APS-YbTa3O9 thermal barrier coatings - Kazuma OKUNO; Masayuki ARAI; Kiyohiro ITO; Tatsuo SUIDZU; Yoichiro HABU (Nihon Kikai Gakkai ronbunshu, 2022)
An advanced thermal barrier coating development is demanded for achieving the next generation gas turbine with a high efficiency. As one of many candidates in TBCs, RTa3O9 in a perovskite-type oxide attracts attention owing to the low thermal conductivity. In this study, thermal and mechanical properties of YbTa3O9 deposited by atmospheric plasma spraying process as a typical GT coating process were investigated via a high-temperature exposure test. The results obtained in this study are as follows: (1) High temperature exposure tests were carried out on freestanding ceramic sample (TC sample) which was extracted chemically from TBC sample. It was found that porosity of the TC sample was not changed significantly with exposure temperature under the fixed exposure time 100h. (2) Young's modulus of the as-sprayed TC sample was 23 GPa, and the associated thermal conductivity was 0.6 W/mK. Those material properties were increased monotonically with exposure temperature under exposure time 100 h, in spite of the porosity having no influence of the exposure temperature. (3) X-ray crystallographic analysis revealed that the crystallization of YbTaO4 caused significant shrinkage of TC material which leads to increasing thermal conductivity. It is therefore desirable to stabilize the microstructure at high temperatures in the future.